2005
DOI: 10.1111/j.1468-2508.2005.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The Skeptical American: Revisiting the Meanings of Trust in Government and Confidence in Institutions

Abstract: This paper critically analyzes the survey literature on trust in government and confidence in institutions. It highlights the gap between theoretical understandings of trust which encompass trust, lack of trust, and distrust, next to empirical realizations which fail to consider active distrust of government. Using a specially tailored survey designed for this project, the paper is the first which directly compares competing operationalizations of trust and distrust. The most frequently used measures, both fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
202
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(232 citation statements)
references
References 22 publications
13
202
0
9
Order By: Relevance
“…For three of the four samples, the model that split trustworthiness constructs into positive and negative types fit better (according to AIC and BIC non-nested comparison indices) than a model with the same degrees of freedom, but using an ability/warmth topical split. This finding is consistent with prior theorizing that trust and distrust are distinct and separable constructs (Cook & Gronke, 2005;Van De Walle & Six, 2013). Alternatively, however, the separation of positive and negative items could reflect a measurement artifact, much in the way that a "difficulty" factor sometimes emerges, not because items vary in content but because they differ in likelihood of endorsement (Saxe & Weitz, 1982).…”
Section: Model May Have Included Identificationsupporting
confidence: 87%
“…For three of the four samples, the model that split trustworthiness constructs into positive and negative types fit better (according to AIC and BIC non-nested comparison indices) than a model with the same degrees of freedom, but using an ability/warmth topical split. This finding is consistent with prior theorizing that trust and distrust are distinct and separable constructs (Cook & Gronke, 2005;Van De Walle & Six, 2013). Alternatively, however, the separation of positive and negative items could reflect a measurement artifact, much in the way that a "difficulty" factor sometimes emerges, not because items vary in content but because they differ in likelihood of endorsement (Saxe & Weitz, 1982).…”
Section: Model May Have Included Identificationsupporting
confidence: 87%
“…First, there have been studies the origins of trust, or distrust; in other words, the identification of which attributes of citizens determine whether or not they trust in government or other democratic institutions. This literature has examined a wide variety of possible covariates of trust in government, and has generally concluded that trust in government is tied closely with the political orientations and evaluations of citizens (Stokes 1962;Citrin and Lukes 2001;Brewer and Sigelman 2002;Cook and Gronke 2005). Despite some contradictory findings by Abramson (1983), Hetherington (1998), and Brewer and Sigelman (2002), most research on trust in government suggests that social situations and demographic attributes do not influence individual trust (Stokes 1962;Citrin and Lukes 2001;Cook and Gronke 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have focused on the apparent decline in the overall level of American trust in government, reflected in particular in the National Election Survey's timeseries of questions on this topic. Although much has been written about the decline in trust in government, it's origins, and the consequences, it is clear that there is a common theme that resonates with the research on the simple cross-sectional analysis of government trust (c.f., Miller 1974aMiller , 1974bCitrin 1974): changes in trust in government are related to changes in the political environment and citizen evaluations of that environment, no matter what we make of the broader implications of these changes (Chanley, Randolph and Rahn 2000;Cook and Gronke 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Más vinculado con las preocupaciones de este trabajo, una legión de estudios en Estados Unidos ha explorado la relación entre hostilidad mediática, ideología política y partidismo. Esta literatura reporta que las personas con ideologías conservadoras así como los republicanos, perciben la presencia de un sesgo hostil -liberal y/o prodemócrata-en los medios y, por lo tanto, manifiestan menores niveles promedio de confianza (Jones, 2004;Cook y Gronke 2007;Lee 2010). Esta asociación se explica porque, en Estados Unidos, el periodismo es considerado una profesión "liberal" y se supone, entonces, que los medios sesgan la cobertura de noticias hacia la izquierda.…”
Section: La Confianza De La Opinión Pública En Los Medios De Comunclassified